Новый вид рода Diacyclops (Crustacea, Copepoda) из Закавказья - Монченко, В.И. (Вестник зоологии, 1985)
D. imparilis sp. n. allied to Macedonian D. minutissimus sensu Petkovski (1954) comb. n. and Japanese D. yezoensis comb. n. (pro Speocyclops yezoensis Ito, 1954) by characters of P₅, endopod P₄, furcal rami, anal operculum and, especially, to the last one by P₁-P₄ segmentation and their spine armature. Majority of these characters are diagnostic to the whole genus Diacyclops. The new species connects the mentioned ones with the rest of the genus Diacyclops due to transitive segmentation of P₁-P₄ (2/2, 2/2, 3/2, 3/2 instead of 2/2, 2/2, 2/2, 2/2 in D. petkovskii), complete (for all Diacyclops species) spine and setal armature of exopods P₁-P₄ distal joints (setae 5-5-4-4 instead of 4-3-4-3 in D. yezoensis).